2021
DOI: 10.3390/su13052738
|View full text |Cite
|
Sign up to set email alerts
|

The Conservational State of Coastal Ecosystems on the Mexican Caribbean Coast: Environmental Guidelines for Their Management

Abstract: The accelerated rate of environmental degradation of the Mexican Caribbean coast is alarming. In this work, spatial analysis procedures were applied to study relationships among wave and wind climates, water quality, and environmental degradation of the principal coastal ecosystems. We found an increasing North-South gradient in the preservation state of the coastal ecosystems, related to the degree of anthropization of the coastline. In the north, all analysed stressors exert high pressure on coral reefs, sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 79 publications
(116 reference statements)
0
15
0
2
Order By: Relevance
“…Stable isotopes (δ 15 N) indicate the assimilation of sewage by different organisms including T. testudinum (Carruthers et al, 2005;Pérez-Gómez et al, 2020). Based on a field survey data review, Guimarais et al (2021) also found a northward deterioration in the coastal ecosystem state, deduced from several metrics including the state of coral reefs and the presence of "climax" Thalassia testudinum habitats. However, data on the pattern of eutrophication along the coast was not very consistent, 124 samples at various locations over 1991 to 2018 did not show a clear north-south gradient (Guimarais et al, 2021) and were inconsistent even at local scales.…”
Section: North-south Seagrass Variation Associated With a Gradient Of Anthropogenic Impactmentioning
confidence: 96%
See 3 more Smart Citations
“…Stable isotopes (δ 15 N) indicate the assimilation of sewage by different organisms including T. testudinum (Carruthers et al, 2005;Pérez-Gómez et al, 2020). Based on a field survey data review, Guimarais et al (2021) also found a northward deterioration in the coastal ecosystem state, deduced from several metrics including the state of coral reefs and the presence of "climax" Thalassia testudinum habitats. However, data on the pattern of eutrophication along the coast was not very consistent, 124 samples at various locations over 1991 to 2018 did not show a clear north-south gradient (Guimarais et al, 2021) and were inconsistent even at local scales.…”
Section: North-south Seagrass Variation Associated With a Gradient Of Anthropogenic Impactmentioning
confidence: 96%
“…A reasonable estimate for the coverage of high LAI canopies (LAI > 3) is the average of 2017 and 2020, giving ∼40 km 2 in 900 km 2 of shallow coastal lagoon. Guimarais et al (2021) provided a figure of 576 km 2 of "seagrass meadows" in the Mexican Caribbean, which in our analysis is the area of estimated LAI greater than 0.7 (563 km 2 ). This is consistent with a presence-absence threshold for Thalassia testudinum since in mixed canopy other macrophytes may contribute around 0.5 to LAI (Supplementary Figure 1).…”
Section: Leaf Area Index-depth Regimementioning
confidence: 97%
See 2 more Smart Citations
“…Typhlatya dzilamensis is not federally listed and yet was here found to be distinct from all other species, representing the only high salinity species with a habitat range restricted to coastal systems throughout the Peninsula. Thus, T. dzilamensis is an excellent candidate in need of evaluation, given its association with karst coastlines, which are particularly vulnerable to anthropogenic impacts and coastal development changes 68,72,73 . Lastly, the identification of two unknown species, which were 'rare' among our newly sequenced samples and in previously published data, warrants further study to better understand their distributions and population genetic structure.…”
Section: Implications For Continuing Integrative Researchmentioning
confidence: 99%